Sovereign external borrowing and multilateral lending: Dynamics and crises - Leopoldo Avellán; Arturo José Galindo Andrade; Giulia Lotti (Inter-American Development Bank (IDB), 2018)
Fiscal policy is procyclical in developing countries. An ample literature has explained this fact and explored its consequences for aggregate cyclical fluctuations. Multilateral Development Banks (MDBs) are an important source of finance for governments and therefore play a role in the execution of fiscal policy. In this paper, we assess whether MDB disbursements to the sovereign commove with government expenditure and with private sovereign lending, during different stances of fiscal policy and during fiscal crises. We find that multilateral lending to the sovereign is correlated with government expenditure and this correlation does not change if the government is running a surplus or a deficit. However, when the sovereign is having a fiscal crisis associated with unsustainable fiscal policy, this relationship disappears for Regional Development Banks (RDBs) and the World Bank (WB). Finally, we find evidence of synchronization between MDBs and IMF during fiscal crises.
Keywords: F21; F34; F41; F44; F53; 330; International government debt; capital flows; multilateral development banks